Governing sustainable school to work transitions: Lessons for the EU - Günther Schmid; Lutz Bellmann; Bernard Gazier; Janine Leschke (Institute of Labor Economics (IZA), 2023)
The European Commission declared 2022 the "European Year of Youth." Apart from the obvious aim to enhance its visibility and political legitimacy, the Commission responded to the fact that COVID-19 badly affected especially young people, manifested in the rise of youth unemployment and of youth neither in employment nor in education or training (NEET). The future of young people at all levels of education - especially of the lowskilled and low-educated - is at stake. They must be prepared for the digital revolution accelerated both by the pandemic and the politically enforced transformation of the industrial economy to a sustainable economy that cares both for a healthy ecology as well as for a healthy society. Alongside its 2019-initiative of the "European Green Deal" the Commission established the "Just Transition Fund" aimed at caring for equitable and efficient transitions from fossil to renewable forms of energy, and alongside its 2020-initiative "Next Generation EU" the Commission aims at a "sustainable recovery" from the Corona pandemic to promote the green and digital transition under the condition of "social fairness". Moreover, in 2020, the Commission made the successful transition from school to work a key priority by reinforcing its Youth Guarantee from 2013. Whereas these initiatives are laudable, experiences so far reveal great deficits in implementation. The increasing complexity of how to navigate young people successfully from school to work is not well understood. The theory of Transitional Labour Markets (TLM), we claim, helps not only to get a structured view of this complexity but promises also plausible strategies for just transitions for youth into decent work.
Keywords: J21; J38; J4; J48; J68; R28; 330; transitional labour markets; labour market policy; youth guarantee; apprenticeships; vocational education and training; just transitions; governing social risks; Europe